Re-examining Religiosity as a Protective Factor: Comparing Alcohol Use by Self-Identified Religious, Spiritual, and Secular College Students - Burke, Adam (Journal of religion and health, 2014)
Religiosity has been found to be associated with lower alcohol use by college students. The majority of studies on this topic, however, fail to differentiate religiosity and spirituality. This is potentially problematic due to the changing face of religion in America today. A study was conducted to explore similarities and differences between self-identified religious and spiritual college students. A modified version of the Core Alcohol and Drug Survey was administered online with a sample of 2,312 students. As hypothesized, self-identified religious and spiritual students differed significantly on key variables related to religious practices, alcohol consumption, and postmodern social values.